Handbook of Combustion 2010
DOI: 10.1002/9783527628148.hoc007
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Kinetic Modeling

Abstract: Combustion is a complex phenomenon characterized by the interaction and competition of various physical and chemical processes. The correct description of chemical changes requires the application of reaction mechanisms that consist of several hundreds or thousands of elementary reactions. This creates an opportunity for kinetic modeling to play important role in understanding the combustion phenomenon. This chapter provides an overview of combustion modeling, the main aim being to present a comprehensive know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Further experiments had shown that, for water [10,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] et. all., for fuels and other liquids [34][35][36][37][38][39][40][41][42][43][44][45][46][47] the evaporation of a droplets takes place in a wide range of boundary conditions when taking into account the influence of environmental characteristics and the heat transfer boundary conditions of the droplets. Pure fuel [39], diesel and biodiesel [42,43], kerosene [44][45][46], various oils [37,38], fuel mixtures [35,41], and other multi-component fuel droplets [34,47] are popular subjects of experimental and theoretical studies of the fuel droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Further experiments had shown that, for water [10,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] et. all., for fuels and other liquids [34][35][36][37][38][39][40][41][42][43][44][45][46][47] the evaporation of a droplets takes place in a wide range of boundary conditions when taking into account the influence of environmental characteristics and the heat transfer boundary conditions of the droplets. Pure fuel [39], diesel and biodiesel [42,43], kerosene [44][45][46], various oils [37,38], fuel mixtures [35,41], and other multi-component fuel droplets [34,47] are popular subjects of experimental and theoretical studies of the fuel droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Many thermal technologies are based on by droplets heat transfer and phase transformations. Therefore, researchers' attention for water heat transfer processes and for heat exchange and phase transformations of hydrocarbon and other liquids dispersed into droplets do not decrease [1][2][3][4][5][6]. A liquid droplets phase transformation cycle combines condensing, unsteady and equilibrium evaporation modes τ ≡ 0 ÷ τ co ÷ τ nf ÷ τ f .…”
Section: Introductionmentioning
confidence: 99%
“…The issue is not raised even in the latest review of combustion kinetic modeling. 3 As a result, a further aspect addressed herein concerns the nature of the potential value of these models. Are they already more than adequate as engineering tools, and can they convey any insight into the chemistry of combustion, which seems to be a growing interpretive temptation?…”
Section: ■ Introductionmentioning
confidence: 99%
“…The fact that this is never generally commented upon, especially when it is clearly apparent that many of these models are chemically flawed, forms the basis of this paper. The issue is not raised even in the latest review of combustion kinetic modeling . As a result, a further aspect addressed herein concerns the nature of the potential value of these models.…”
Section: Introductionmentioning
confidence: 99%